Modeling of milled straw heap separation in air-flow classificator with three pneumatic ducts - Yury I. Yermolyev; Artem A. Doroshenko; Sergey V. Belov (Advanced Engineering Research)
The research subject is a multivariate analysis of the air-flow classification process of the straw heap with a predetermined fractional composition supplied to the cleaning after the drum destroyer. The work objective is to identify patterns of the air separation using three pneumatic ducts with a linkage parameter variation. The investigative technique is an analytical modeling. The effect of probabilistic characteristics of the heterogenic thrashed heap supply, airflow velocity distribution by the separator width, and density function of heap components terminal velocity on the separation is evaluated. The air-flow classification process on each section of the pneumatic duct is considered. To this end, the mathematical expressions averaging the air classification indicators of the consistently functioning three pneumatic ducts and a stochastic quasistatic mathematical model of the separator operation with three pneumatic ducts in series are used. The results of the separator parametric synthesis and its technological parameters are presented. The fractional constituents of the heap components and their percent-sizes in each air-classified fraction are shown. The possibility of the air-flow classification of the crushed straw heap in the predetermined factions at the preset productivity of 0.6-0.7 kg/m∙s is revealed. It is found that under the rational functioning of the air separator, the straw content in the service faction is 97.03%. In this case, the minimum grain content is 0.03%, and mineral impurities are 0%. It is revealed that the air separator with three pneumatic ducts in series is sufficient for separating the crushed straw heap with the predetermined agro-technical requirements.